2016
DOI: 10.1097/ico.0000000000000937
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Endothelial Layer in the Deswelling Process of Organ-Cultured Human Corneas Before Transplantation

Abstract: Corneal dehydration after organ culture seems to be a multifactorial process, which not only depends on osmotic effects of the deswelling compound but also requires the presence of an intact endothelial cell layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
10
1
Order By: Relevance
“…All three corneas followed the same thickness profile, with an initially rapid decrease for approximately 3 hours caused by the osmotic de-swelling due to the hypertonic dextran solution. After this minimum, there was a slower increase in the thickness of the cornea [ 19 ], which was associated with dextran diffusing into the cornea [ 44 ], changing the osmotic balance. The temporal sampling period of the thickness measurements of de-swelling corneas, by this automated method, is much smaller (1 versus 30 minutes [ 30 ]) than has previously been presented.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All three corneas followed the same thickness profile, with an initially rapid decrease for approximately 3 hours caused by the osmotic de-swelling due to the hypertonic dextran solution. After this minimum, there was a slower increase in the thickness of the cornea [ 19 ], which was associated with dextran diffusing into the cornea [ 44 ], changing the osmotic balance. The temporal sampling period of the thickness measurements of de-swelling corneas, by this automated method, is much smaller (1 versus 30 minutes [ 30 ]) than has previously been presented.…”
Section: Resultsmentioning
confidence: 99%
“…To counteract this, donor corneas are “de-swelled” before use in a hypertonic solution, usually containing dextran, which removes the excess water from the cornea by osmosis. The health of the endothelial layer affects the de-swelling rate [ 19 ] and conversely, the de-swelling process can damage the health of the donor tissue [ 20 ]. For these reasons there has been substantial research to optimise the de-swelling time [ 9 , 21 ], improve the method [ 10 ], or use alternative osmotic agents such as poloxamers or PEG [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Other investigations employed OCT-based methods because they enable the measurement of corneoscleral buttons under sterile conditions. [24][25][26][27] LASIK interfaces could be detected within the reflection pattern of the stromal tissue. Beyond that, Lin et al estimated anterior and posterior curvatures by means of a parabolic fit.…”
Section: Introductionmentioning
confidence: 91%
“…The deswelling of organ-cultured corneal tissue was investigated by Schnitzler et al who found that the condition of the endothelium might have a significant effect on the deswelling aside from the osmotic effect of the culture medium. 27 Thus, measuring corneal thickness before reimmersement and at a standardized time after reimmersement might be one indicative factor for endothelium activity.…”
Section: Corneal Parametersmentioning
confidence: 99%
See 1 more Smart Citation